2021
DOI: 10.3748/wjg.v27.i12.1194
|View full text |Cite
|
Sign up to set email alerts
|

Cytapheresis re-induces high-rate steroid-free remission in patients with steroid-dependent and steroid-refractory ulcerative colitis

Abstract: BACKGROUND It is a crucial issue for patients with refractory ulcerative colitis (UC), including steroid-dependent and steroid-refractory patients, to achieve and maintain steroid-free remission. However, clinical studies focused on the achievement of steroid-free remission in refractory UC patients are insufficient. Cytapheresis (CAP) is a non-pharmacological extracorporeal therapy that is effective for active UC with fewer adverse effects. This study comprised UC patients treated with CAP and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…Moreover, intensive, twice‐a‐week GMA, proved more effective than the standard once‐a‐week schedule, in inducing mucosal healing and long‐term maintenance of remission in the absence of steroids 17 . Reducing the interval between sessions worked again in case of relapse 18 . These data support the conclusion of a previous meta‐analysis reporting that GMA is superior to corticosteroids in inducing clinical remission (OR 2.23) 38 .…”
Section: Efficacy Of Adsorptive Cytapheresis In Ulcerative Colitissupporting
confidence: 75%
See 1 more Smart Citation
“…Moreover, intensive, twice‐a‐week GMA, proved more effective than the standard once‐a‐week schedule, in inducing mucosal healing and long‐term maintenance of remission in the absence of steroids 17 . Reducing the interval between sessions worked again in case of relapse 18 . These data support the conclusion of a previous meta‐analysis reporting that GMA is superior to corticosteroids in inducing clinical remission (OR 2.23) 38 .…”
Section: Efficacy Of Adsorptive Cytapheresis In Ulcerative Colitissupporting
confidence: 75%
“…In some centers, a single‐needle, single‐catheter technique, involving the use of a pump equipped with a valve controlling the direction of blood flow has been used 16 . The procedure is usually performed on a weekly basis, but more aggressive, twice‐a‐week strategies have been proposed to foster efficacy 17,18 …”
Section: Mechanisms Of Action Of Adsorptive Cytapheresismentioning
confidence: 99%
“…Although the background of the patients in these studies were different, the remission rates in CAP therapy ranged from 40.3%-73% (mean ± SD: 56.25 ± 16.03%, median: 55.85%, interquartile range: 41.475%-71.425%) and the steroid-free remission rates in CAP therapy ranged from 36%-56.3% (mean ± SD: 47.25 ± 9.99%, median: 48.35%, interquartile range: 37.425%-55.975%) (Figure 1 ). Among these studies, four[ 37 , 42 , 58 , 59 ] compared the rates of clinical remission between the patients exposed to thiopurines or IM and the patients unexposed to them. In all four studies significant differences were not observed in the rates of remission between patients exposed to thiopurines or IM and control.…”
Section: Efficacy Of Cap In Patients With Uc Showing Insufficient Res...mentioning
confidence: 99%
“…Regarding the rate of steroid-free remission, two studies[ 59 , 62 ] compared the rates of steroid-free remission between the patients concomitantly treated with thiopurines or IM and the patients treated without them. These studies showed that significant differences were not observed between the patients concomitantly treated with thiopurines or IM and patients treated without them.…”
Section: Efficacy Of Cap In Patients With Uc Showing Insufficient Res...mentioning
confidence: 99%
See 1 more Smart Citation